Abiotrophia defectiva and Granulicatella: A Literature Review on Prosthetic Joint Infection and a Case Report on A. defectiva PJI and Concurrent Native Valve Endocarditis - Cristina Seguiti; Edda Piacentini; Angelica Fraghì; Mattia Zappa; Elia Croce; Angelo Meloni; Marco Cirillo; Clarissa Ferrari; Chiara Zani; David Belli; Tony Sabatini; Paolo Colombini (Microorganisms)
Together with Granulicatella spp., A. defectiva was formerly classified within the group of nutritionally variant streptococci (NVS). NVS-related endocarditis has been associated with higher rates of complications, bacteriological failure, and mortality compared to other streptococci, partially due to challenges related to timely and accurate identification. PJI caused by A. defectiva are rarely reported, and standardized management strategies have not yet been established. We describe a case of a 68-year-old man with concomitant A. defectiva PJI and native mitral valve endocarditis. The patient was managed conservatively for endocarditis and subsequently underwent a two-stage arthroplasty of the infected prosthetic knee. A. defectiva was identified using MALDI-TOF mass spectrometry on both synovial fluid and blood cultures. As penicillin susceptibility data were not available, the patient was treated with vancomycin at a dose of 2 g/day, resulting in a favorable clinical response. In addition, we performed a literature review on A. defectiva and Granulicatella PJI. Despite the limited number of reported cases in the literature, the findings suggest a potential correlation between clinical outcomes and antimicrobial treatment duration. Further comprehensive studies are needed to establish standardized management strategies for A. defectiva and Granulicatella PJI.